Parasites and steroid hormones: corticosteroid and sex steroid synthesis, their role in the parasite physiology and development - Romano, Marta C.; Jiménez, Pedro; Miranda, Carolina; Valdez, Ricardo A. (Frontiers in Neuroscience, 2015)
In many cases parasites display highly complex life cycles that include establishment of the larva or adults within host organs, but even in those that have only one host reciprocal intricate interactions occur. A bulk of evidence indicates that steroid hormones influence the development and course of parasitic infections, the host gender susceptibility to the infection and the associate differences in immunological response are good examples of the host-parasite interplay. However, the capacity of these organisms to synthesize their own steroidogenic hormones still has more questions than answers. It is now well known that many parasites synthesize ecdysteroids, but limited information is available on sex steroid and corticosteroid synthesis. This review intends to summarize some of the existing information in the field. In many but not all parasitosis the host hormonal environment determines the susceptibility, the course and severity of parasite infections. In most cases the infection disturbs the host environment, and activate immune responses that finally affect the endocrine system. Furthermore, sex steroids and corticosteroids may also directly modify the parasite reproduction and molting. Available information indicates that parasites synthesize some steroid hormones like ecdysteroids and sex steroids and the presence and activity of related enzymes have been demonstrated. More recently, the synthesis of corticosteroid like compounds has been shown in Taenia solium and tapeworms and in Taenia crassiceps WFU cysticerci. Deeper knowledge of the endocrine properties of parasites will contribute to understand their reproduction and reciprocal interactions with the host, and also may contribute to design tools to combat the infection in some clinical situations.